2005
DOI: 10.1016/j.ydbio.2005.07.019
|View full text |Cite
|
Sign up to set email alerts
|

The duality of β-catenin function: A requirement in lens morphogenesis and signaling suppression of lens fate in periocular ectoderm

Abstract: In the current analysis, we have investigated both the cytoskeletal and signaling roles of beta-catenin during the early phases of lens development using conditional loss- and gain-of-function strategies. Conditional loss of beta-catenin in the presumptive lens does not perturb the normal sequential appearance of lens fate markers but results in a dramatic failure of the coordinated epithelial cell behavior that constitutes lens morphogenesis. Similarly, loss-of-function for Lrp6, the Wnt pathway coreceptor ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
178
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(214 citation statements)
references
References 48 publications
32
178
1
3
Order By: Relevance
“…Analyses of specific neural crest and neuroectoderm markers would reveal this uncertainty. In agreement, loss of b-catenin activity in the presumptive lens and extraocular ectoderm using the Lens-Cre construct does not perturb lens fate decision, but leads to formation of small ectopic lentoids expressing Pax6 and crystallin proteins in the extraocular ectoderm [63,64]. The overall conclusion is that between gastrula stages and lens placodal stages Wnt activity restricts caudal expansion of lens formation (figure 3).…”
Section: Caudal Restriction Of Lens Cells By Wnt Activitymentioning
confidence: 53%
See 2 more Smart Citations
“…Analyses of specific neural crest and neuroectoderm markers would reveal this uncertainty. In agreement, loss of b-catenin activity in the presumptive lens and extraocular ectoderm using the Lens-Cre construct does not perturb lens fate decision, but leads to formation of small ectopic lentoids expressing Pax6 and crystallin proteins in the extraocular ectoderm [63,64]. The overall conclusion is that between gastrula stages and lens placodal stages Wnt activity restricts caudal expansion of lens formation (figure 3).…”
Section: Caudal Restriction Of Lens Cells By Wnt Activitymentioning
confidence: 53%
“…Consistently, even in the presence of Wnt inhibitors prospective lens cells in chick explants still upregulate the lens markers L-Maf and d-crystallin (Sjö dal and Gunhaga 2006, unpublished data). Finally, in mice, individual deletions of two Wnt co-receptors, Lrp5 and Lrp6 required for Wnt canonical signalling, do not perturb lens fate determination [64][65][66]. Although, a double knock-out of Lrp5 and Lrp6 would determine whether these co-receptors may act redundantly during early lens specification, it seems unlikely that such double mutants would exhibit a lens phenotype, since the above results clearly provide evidence that Wnt signals are not required for lens fate specification.…”
Section: Caudal Restriction Of Lens Cells By Wnt Activitymentioning
confidence: 85%
See 1 more Smart Citation
“…An important aspect to both lens development and lens regeneration is the differentiation of lens fiber cells. In the case of lens development, the Wnt/β-catenin signaling pathway appears essential for the differentiation of the lens epithelium into lens fiber cells [34][35][36]. Mice with a homozygous null mutation in the lrp6 co-receptor gene are unable to fully undergo differentiation of the lens epithelium [35].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Dickkopfs antagonize the pathway by binding to the LRP co-receptor and preventing the stabilization of the β-catenin complex. A study examining β-catenin function in lens development found that loss of β-catenin function in the periocular ectoderm of embryonic mice results in ectopic lentoid body formation [36].…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%